Novel design and development of PDMS-glass hybrid microfluidic devices for continuous double encapsulation of liquid-oil droplets - Lim, Chang Nong (2019)
Microfluidics have been a topic studied intensely until current by most of the researchers due to its broad application in different industry sector. Comparing to the conventional bulk method, fabrication of double emulsion droplets using microfluidic technique is the highly sought-after method as it provides a flexible platform which enabled the generation of highly monodispersed droplets. Current technology shows establishment on glass capillary and polydimethylsiloxane (PDMS) microfluidic device, while the researchers continue to develop simple and facile platform with different materials competent to their applications. Multiphase flow was involved in generating the double emulsion droplets and hence the significance of the fluid wetting properties and the intrinsic properties of the respective material. Localised surface treatment in a one-chip configuration microfluidic device, however, is a complex procedure which involves expensive chemicals with short recovery period. Therefore, this thesis aimed to develop and fabricate a cost-effective hybrid microfluidic device, able to generate monodisperse W/O/W double emulsion droplets without chemical surface treatment. By utilising the two commonest materials i.e. glass capillary tube and PDMS, a PDMS-Glass Capillary Hybrid Microfluidic Device (PGHD) was developed. To further establish the system, the standard operating procedure (SOP) was developed to enable definite start-up of the experiment. On top of that, the fabrication methodology was optimised to improve the efficiency and precision. The design geometry was modified and optimised accordingly to ensure the practicability of the PGHD. Quantitative experimental analysis was carried out to understand the flow profile and droplet behaviour in the PGHD, which then enable the manipulation of the parameters such as flow rate ratio accordingly to achieve the desired number of encapsulation.